Nanocolumnar association and domain formation in porous thin films grown by evaporation at oblique angles. (18th August 2016) - Lopez-Santos, C; Alvarez, R; Garcia-Valenzuela, A; Rico, V; Loeffler, M; Gonzalez-Elipe, A R; Palmero, A
Abstract: Porous thin films grown at oblique angles by evaporation techniques are formed by tilted nanocolumnar structures which, depending on the material type and growth conditions, associate along certain preferential directions, giving rise to large domains. This arrangement, commonly denoted as bundling association, is investigated in the present work by performing fundamental experiments and growth simulations. It is proved that trapping processes of vapor species at the film surface, together with the shadowing mechanism, mediate the anisotropic widening of the nanocolumns and promote their preferential coalescence along certain directions, giving rise to domains with different shape and size. The role of these two processes is thoroughly studied in connection with the formation of these domains in materials as different as SiO2 and TiO2 .